The Brazilian pediatric myelodysplastic cooperative group strategies: are they relevant to improve educational approach and correct diagnosis? - Lopes, L. F.; Lorand-Metze, I; Niero-Melo, L.; Tone, L. G.; Velloso, E.; Campanaro, C. M.; Latorre, M. D. (Elsevier B.V., 2002)
Brazil is a wide country with huge contrasts. Its peculiarities can highlight environmental factors that could influence the frequencies of different cancers. The standard treatment and results achieved from several different areas of the country may not be found in others. The establishment of a national cooperative group has the potential to improve outcomes. The The Brazilian Cooperative Group on Pediatric Patients with Myelodysplastic Syndrome (BCG-MDS-PED) was first organized in January 1997 as a working group of hematologists, pediatric oncologists, pediatric-hematologists, molecular biologists and other professionals in order to study pediatric (age < 18 years) MDS. Six distinct subcommittees constituted with members from several universities: cytology, histopathology, clinical, cytogenetics, molecular biology and epidemiology. The goals of the BCG-MDS-PED were: (i) to offer support for diagnosis and orientation for treatment; (ii) educational Support for the colleagues all over the country and (iii) research on pathogenesis and new approaches for pediatric MDS patients. There are socio-economical differences among the five regions of the country. The BCG-MDS-PED believes that it is absolutely necessary to Study the clinical, cellular, molecular and epidemiological aspects of MDS, taking in account these peculiar differences among populations and regions. Since 1997, 114 pediatric cases were referred to the BCG-MDS-PED from 21 centres. Seven Brazilian states have sent cases to the group, 31 patients were referred from universities, 73 patients from pediatric oncology units (foundations) and 10 patients came from private clinics. Some of these patients have been followed up and/or treated by the physician who referred them to the BCG-MDS-PED for confirmation of the initial diagnosis. The majority of these physicians have required orientation on diagnostic and treatment issues, as well as to complete cytogenetic and molecular studies. From these 114 patients, 64 patients were confirmed as MDS. We believe that, the more numerous the MDS-studied cases, the more experienced will be the referee group on clinical and laboratory features on childhood MDS in Brazil. (C) 2002 Published by Elsevier B.V. Ltd.
Keywords: pediatric MDS; myelodysplastic syndrome; pediatric myelodysplasia; secondary myelodysplasia; Brazilian pediatric MDS